PERAN KOMITE SEKOLAH DALAM PEMBIAYAAN PENDIDIKAN - Nili Hayani (Manajer Pendididikan, 2015)
The aim of this study were: to describe the role of the school committee as a support, controller, giving consideration and a liaison between the school and the community in terms ofeducation financing and describe the school committee policy in the face financing problems faced school. Research conducted qualitative descriptive approach. The subject of this study wereprincipal, head committe and committe treasurer. The result of this study were: (1) School committee as a support support through funding, mind, and school infrastructure; (2) schoolcommittee as a controller of school building and financial; (3) School committee as giving consideration of infrastructure and school funds; (4) relationship with the community and parentscan be established premises either.Keywords: committee, utilization, education financing.